"I Don't Support It for My Children": Perceptions of Parents and Guardians regarding the Use of Modern Contraceptives by Adolescents in Arua City, Uganda - Godfrey Jalinga Vuamaiku; Joshua Epuitai; Monicah Andru; Mary Aleni (Hindawi Limited, 2023)
Despite the high rates of adolescent pregnancies, the utilization of modern contraceptives is still low among adolescents in Uganda which highlights a missed opportunity for the prevention of unwanted pregnancies among adolescents. We explored the perception of parents and guardians regarding the use of modern contraceptives by adolescents and the roles parents and guardians play in the use of modern contraceptives by the adolescents. A descriptive qualitative study was conducted in one of the suburbs of Arua city in the West Nile subregion in Uganda. Fifteen (15) in-depth interviews were conducted with parents and or guardians to explore their perceptions and roles regarding the use of modern contraceptives by adolescents. Thematic analysis was used in qualitative data analysis. Parents did not support adolescents' use of modern contraceptives. Lack of parental support was related to perceptions that modern contraceptives promote sexual promiscuity, fear that it causes infertility and that it is incompatible with cultural, religious, and moral norms. Parents and guardians opted to emphasize the importance of abstinence, conformity with cultural and religious norms, and the need to focus on completing school instead of encouraging the use of modern contraceptives. Few parents and guardians supported the use of modern contraceptives, specifically condoms, to prevent unwanted pregnancy by the adolescents and parents/guardians, sexually transmitted infections, and early school dropouts. Parents and guardians expressed feelings of inadequacy related to discussions on contraception use with their adolescent children and therefore avoided talking about it. Our study reveals a lack of parental support regarding the use of modern contraceptives among adolescents. Public health interventions which promote intergenerational, socioculturally, and religiously appropriate communication should be instituted in the communities in order to promote sustainable adoption of modern contraceptive use among adolescents.